Flexural performance of cold-formed square tube splice joints connected by self-tapping screws - Wang, Shuaibing; Zhou, Tianhua; He, Dongliang; Zhao, Wenjie; Liao, Tianwei; Sang, Liurui (Structures (Oxford), 2024)
Experimental studies and numerical simulations are performed to investigate flexural performance of cold-formed square tube (CFST) splice joints connected by self-tapping screws. Seven specimens were fabricated from the external steel plate and inner sleeve using self-tapping screws and underwent variations in screw quantity. Refined finite element models were developed and calibrated using a dataset of test results from cold-formed square tube splice joints. Subsequently, an extensive parametric study was undertaken to expand the CFST splice joints data pool, covering the CFST strength, thickness, screw diameter, spacing, as well as the number of rows and columns screws. Finally, a dependable design method for the flexural bearing capacity of CFST splice joints was derived from the experimental and finite element analysis results. The conclusions are as follows: (1) The flexural performance of inner sleeve specimens surpasses that of external steel plate specimens significantly. (2) Variations in steel strength and thickness minimally impacted the flexural bearing capacity of the specimens. Alterations in screw diameter, longitudinal spacing, rows and columns notably influenced the flexural performance of the specimens. (3) A comparison revealed that the proposed design method exhibited higher accuracy and safety in calculating the flexural bearing capacity of CFST splice joints.